Particle size optimization of metal–organic frameworks for superior capacitive deionization in oxygenated saline water. Issue 30 (28th March 2023) - Xing, Zhiyuan; Xuan, Xiaoxu; Hu, Haiyan; Li, Mohua; Gao, Huimin; Alowasheeir, Azhar; Jiang, Dong; Zhu, Liyang; Li, Zhengtong; Kang, Yunqing; Zhang, Jing; Yi, Xibin; et al.
Abstract : The effect of metal–organic framework particle size on capacitive performance in oxygenated saline water was studied, suggesting that as particle size increases, the performance decreases. Abstract : Pyrolysis-free metal–organic frameworks (MOFs) with optimized particle sizes were used as capacitive deionization (CDI) materials in oxygenated saline water. Upon decreasing the particle size of the MOFs, excellent cycling stability and higher CDI performance were achieved. This was possibly due to the improvement in charge transfer and electrolyte permeation, uncovering the significance of particle size control in improving CDI performance.